Hebräisch: biblisch-hebräische Unterrichtsgrammatik - Krause, Martin; Pietsch, Michael; Rösel, Martin (De Gruyter Studienbuch, 2010)
The Grammar is intended as a textbook to support Hebrew classes which gives the teachers the maximum latitude for the selection and application of different teaching methods and for the students simplifies the tasks of learning, looking up and repetition with its clear and transparent ordering of the teaching material. In its design, the work dispenses with a division into lessons, and from the outset bases its processing of the material on the biblical texts. The work is complemented by a comprehensive collection of texts and a highly structured vocabulary. innovativetextbook based on the author´s and editors´ course work two-colour-print provides easy access Martin Krause und Michael Pietsch, Universität Hamburg; Martin Rösel, Universität Rostock.